Peningkatan Keterampilan Menulis Curriculum Vitae (CV) dan Wawancara Kerja Pada Siswa MAN 1 Brebes - Ratri Wikaningtyas; Rony Dharpono; Martselani Adias Sabara (Universitas Kristen Indonesia Toraja, 2024)
This training aims to improve skills in writing a curriculum vitae (CV) and facing job interviews for students at MAN 1 Brebes. The entry of students into the world of work requires good preparation in compiling an attractive CV and facing job interviews with confidence. Training and mentoring methods were used in this study, involving students in effective CV writing exercises and simulated job interviews. The results of the training showed a significant increase in students' ability to write an attractive CV and face job interviews with higher self-confidence. It is hoped that the results of this research can make a positive contribution to the preparation of students for facing challenges in the world of work and increase their chances of getting the job they want.